Aeroexpress public transport system introduction in Almaty and its impact on greenhouse gases emissions decrease in Almaty city transport sector (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In Almaty, there are currently more than 500,000 vehicles registered and there is an average of another 200,000 vehicles that enter the city from outlying Almaty Oblasts during working hours. The road network of Almaty has not grown since 1990 when the municipality estimated the number of cars in Almaty to be 100,000.Almaty public transport system degrade and became ineffective with significant loss of safety and comfort level by the reason of privatization and occurring of “shadow” taxi at the service market. [1]Almaty airport is not connected with railway stations Almaty 1, Almaty 2 and city center by a straight and comfortable public transport route. Thus, the prevailing number of airport visitors prefer travelling on personal transport or taxi. Which is, in turn, brings a negative environmental loads. In current circumstances, the Moscow Aeroexpress transport analogue may become a good solution for Almaty.